Pengaruh Beban Kerja Dan Lingkungan Kerja Fisik Pelayanan Internet Terhadap Kinerja Karyawan Pada PT. Gonet Teknologi Indonesia - Rizka Dwi Saputri; Henni Marlinah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Workload (X1) and Physical Work Environment (X2) on Employee Performance at PT. Gonet Teknologi Indonesia. The method used in this study is a quantitative method. The population in this study amounted to 50 employees, with a sampling technique using saturated samples so that the entire population became respondents with data collection through observation and questionnaires totaling 50 respondents. The results of the study partially show that the workload variable (X1) on Employee Performance (Y) has a regression equation Y = 6.882 + 1.372 X1 with a correlation coefficient of 0.662 indicating a strong relationship with a determination coefficient of 43.90%. Hypothesis testing shows t count> t table (2.804> 2.010), so H0 is rejected and H1 is accepted, meaning there is a significant influence between workload on Employee Performance. Other partial results show that the Physical Work Environment (X2) on Employee Performance (Y) has a regression equation Y = 11.744 + 0.660 X2 with a correlation coefficient of 0.676 which indicates a strong relationship, with a determination coefficient of 45.70%. The hypothesis test shows that t count> t table (3.119> 2.010), so H0 is rejected and H2 is accepted, meaning there is a significant influence between the Physical Work Environment on Employee Performance. Simultaneously, the workload variable (X1) and the Physical Work Environment (X2) on Employee Performance (Y) show the results of the regression equation Y = 4.693 + 0.783 X1+ 0.411 X2 with a correlation coefficient of 0.731 which indicates a strong relationship with a determination coefficient of 53.50%, while 50.1% is influenced by other factors. The hypothesis test shows that the calculated F value> F table (27.021> 3.20), so H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between workload and the Physical Work Environment on Employee Performance at PT. Gonet Teknologi Indonesia